Analisis Economic Value Added (EVA) Perusahaan Sektor Energi di Bursa Efek Indonesia Periode 2013-2022 (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
The Energy sector is one of the sectors in the Indonesian economy and the Indonesia Stock Exchange (IDX). 86 companies listed on the IDX. The sample is to 7 companies. The purpose of the study was to determine the Financial Performance Analysis of Energy sector companies listed on IDX for the period 2013-2022 using Economic Value Added (EVA). Based on calculations, EVA ADRO negative results (EVA0) in 2016-2019 and 2021-2022. AKRA's EVA from 2013-2022 are all positive (EVA>0). EVA HRUM in 2014-2015 was negative (EVA 0). EVA ITMG from 2013-2022 are all positive (EVA>0). EVA MEDC in 2013-2021 is negative (EVA 0). PGAS EVA in 2013-2014 was positive (EVA>0) and 2015-2023 was negative (EVA